2006
DOI: 10.1002/nme.1836
|View full text |Cite
|
Sign up to set email alerts
|

An improved discrete Kirchhoff quadrilateral element based on third‐order zigzag theory for static analysis of composite and sandwich plates

Abstract: SUMMARYA new improved discrete Kirchhoff quadrilateral element based on the third-order zigzag theory is developed for the static analysis of composite and sandwich plates. The element has seven degrees of freedom per node, namely, the three displacements, two rotations and two transverse shear strain components at the mid-surface. The usual requirement of C 1 continuity of interpolation functions of the deflection in the third-order zigzag theory is circumvented by employing the improved discrete Kirchhoff co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Thus, for the kth layer, the displacement field is given by Shu and Sun [40] and Kapuria and Kulkarni [19].…”
Section: The Third-order Zigzag Theory Approximationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, for the kth layer, the displacement field is given by Shu and Sun [40] and Kapuria and Kulkarni [19].…”
Section: The Third-order Zigzag Theory Approximationsmentioning
confidence: 99%
“…R k 1 ,R k 2 ,R 3 andR 4 are 2×2 coefficient matrices which depend on the material properties and lay-ups, whose expressions are given in [19]. For the smeared third order theory (TOT) [34], u can be expressed in the form of Eq.…”
Section: The Third-order Zigzag Theory Approximationsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 and 8. It can be observed that the present zig-zag theory can predict more accurate transverse shear stresses than the zig-zag theory proposed by Kapuria and Kulkarni [27] by integrating the three-dimensional equilibrium equations. In addition, transverse shear stress for five-layer plate is shown in Fig.…”
Section: Transverse Shear Stresses From Three-dimensional Equilibriummentioning
confidence: 84%
“…Akhras and Li (2007) developed a spline finite strip method based on Cho's higher order zigzag theory for the static analysis of the plate. Kapuria and Kulkarni (2007) presented a four node quadrilateral element based on the third order zigzag theory for the analysis of laminates. The need of C 1 continuity requirement is circumvented by using a discrete Kirchoff constraint approach, where the derivaties of transverse displacement are replaced by rotational variables.…”
Section: Introductionmentioning
confidence: 99%